Batwoman : haunted tides - Williams, J. H., III (DC Comics, 2019)
"They call her La Llorona. "The Weeping Woman." A spectral presence that drowns her own sorrow by destroying the lives of others, dragging innocent children to a watery grave...or to an even worse fate. The hero called Batwoman is no stranger to sorrow herself. Estranged from the father who was once her partner in crime-fighting, she blames him for the death of her mad sister in Gotham Harbor-but she blames herself most of all. Now she has a new partner-her cousin Flamebird. Together, they're on the hunt for La Llorona, the children she's abducted and the shadowy forces behind it all. But the hunters are hunted as well: everyone from government agents to Gotham cops wants to clip Batwoman's wings... A tide of danger and death is coming in to Gotham City. And it will be all Batwoman can do to keep her head above water."--